MSME Business Strategy Training in The Digital Era for Kupang Raya Village Community, North Teluk Betung District, Bandar Lampung City - Septa Riadi; Nelson Nelson; Yessi Dekasari; Hujaimatul Fauziah; Trisnowati Josiah (International Journal of Social Service and Research, 2022)
Kupang raya village is a sub-district located in the sub-district of Teluk Betung Utara, Bandar Lampung City. Kupang Raya Village is only 1 KM from the city center of Bandar Lampung, causing most of the population in Kupang Raya to work as entrepreneurs. The majority of businesses run by the community are small and medium enterprises. Most businesses run by community members are still traditional and have not been touched by technology. Sales in the traditional way are indeed decreasing due to pressure from the digital platform sales system. For this reason, MSME business strategy training is needed by introducing MSMEs in Kupang Raya Village with a Digital Platform. The training was carried out employing public lectures and hands-on practice. After the training, participants are expected to be able to apply marketing using a digital marketing platform.